Edoxaban Exposure in Patients With Atrial Fibrillation and Estimated Creatinine Clearance Exceeding 100 mL/min. Issue 5 (7th December 2021) - Yin, Ophelia; Kakkar, Tarundeep; Duggal, Anil; Kotsuma, Masakatsu; Shi, Minggao; Lanz, Hans; Grosso, Michael A.
Abstract: Edoxaban 60 mg is approved for stroke prevention in patients with atrial fibrillation (AF) not fulfilling any dose‐reduction criteria. As edoxaban is partially renally cleared (≈50%), this study compared pharmacokinetics (PK) and pharmacodynamics of edoxaban 60 mg once daily with edoxaban 75 mg once daily in patients with AF with high renal clearance (creatinine clearance > 100 mL/min) over 12 months. Primary PK and pharmacodynamics end points were plasma edoxaban exposure and anti–factor Xa (FXa) concentration. A population PK model estimated edoxaban exposure at steady state. Efficacy and safety outcomes included composites of stroke, transient ischemic attack, systemic embolism, and major and clinically relevant nonmajor bleeding. Of 607 patients, 303 and 304 were randomized to edoxaban 60 and 75 mg, respectively. Edoxaban 75 mg provided ≈25% higher exposure than 60 mg. This increase was accurately depicted in the population PK model; anti–factor Xa concentration correlated with edoxaban exposure. Rates of composite and individual outcomes were similarly low between doses. In conclusion, the 25% increase in edoxaban dose (60‐75 mg) resulted in ≈25% exposure increase in the 75‐mg group. Higher exposure was not associated with reduced stroke risk in patients with AF with high renal clearance.